The Impact of Marketing Education Integration with Industry in Improving Student Career Readiness - Andriya Risdwiyanto; Bambang Sugeng Dwiyanto; Jemadi Jemadi; Djoko Wijono; Etty Sri Hertini (Indo-MathEdu Intellectuals Journal, 2023)
Education is one of the main pillars in the development of a country's human resources. The integration of education with industry is one of the crucial aspects to be considered. This study aims to explore and analyse the impact of marketing education integration with industry in improving students' career readiness. This research is a literature review that uses a qualitative method approach, which means it will analyse and interpret data by relying on information and text from various sources. The study results show that the integration of marketing education with industry has a significant positive impact in improving students' career readiness. These measures include practical skills development, soft skills enhancement, professional network building, and maintaining curriculum relevance to the dynamic world of work. The importance of this integration cannot be overlooked in the effort to prepare students to compete in the competitive marketing industry.